A randomized clinical trial of the safety and efficacy of sitagliptin in patients with type 2 diabetes mellitus inadequately controlled by acarbose alone. (3rd April 2017) - Wang, Weiqing; Ning, Guang; Ma, Jianhua; Liu, Xiaomin; Zheng, Shaoxiong; Wu, Fan; Xu, Lei; O'Neill, Edward A.; Fujita, Kenji P.; Engel, Samuel S.; Kaufman, Keith D.; Shankar, R. Ravi
Abstract: Objective: To evaluate the safety and efficacy of sitagliptin when added to the treatment of patients with type 2 diabetes mellitus (T2DM) and inadequate glycemic control on acarbose monotherapy. Research design and methods: This was a multicenter, randomized, placebo-controlled, double-blind clinical trial. Patients ( N  = 381) with T2DM and inadequate glycemic control (glycated hemoglobin [HbA1c] ≥ 7.0% and ≤10.0%) on acarbose monotherapy (at least 50 mg three times daily) were randomized in a 1:1 ratio to receive the addition of sitagliptin 100 mg or matching placebo once daily for 24 weeks. Main outcome measures: Changes from baseline in HbA1c and fasting plasma glucose (FPG) at Week 24. Results: The mean baseline HbA1c in randomized patients was 8.1%. At Week 24, the placebo-controlled, least squares mean changes from baseline (95% confidence interval) in HbA1c and FPG in the sitagliptin group were −0.62% and −0.8 mmol/L ( p  < .001), respectively. At Week 24, 37.8% of patients in the sitagliptin group were at HbA1c goal of <7% compared with 17.2% in the placebo group ( p  < .001). Sitagliptin was generally well tolerated, and there were no significant between-group differences in prespecified safety parameters (symptomatic hypoglycemia, diarrhea, abdominal pain, nausea, vomiting). A higher incidence of serious adverse events was observed in the sitagliptin group (5.2%) relative to placebo (0.5%); all but one, in the sitagliptin group, were not considered related to drug. Conclusions: Sitagliptin was generally well tolerated and provided statistically superior and clinically meaningful improvements in glycemic control after 24 weeks of treatment compared to placebo when added to treatment of patients with inadequate glycemic control on acarbose monotherapy. Clinicaltrials.gov: NCT01177384.